Rainwater Harvesting Potential at the University of Eldoret, Kenya - Tsuma , Esther I.; Odenyo , Victor A. O.; Ouma- Odero , Douglas (African Journal of Education,Science and Technology (AJEST), 2015)
Water is a vital resource in the environment and only 3% of all water on Earth is fresh water, all of which comes from rains. Water keeps the environment “alive”, and plays a key role in environmental sustainability. Proper harnessing of water has benefits which contribute to meeting our millennium development goals on water and environmental sanitation, promote sustainability, reduce annual expenditure on water and recharge underground aquifers. One of the ways to reduce dependence on municipal sources of water is through rainwater harvesting (RWH), defined as the collection, conveyance, and storage of rainwater for an intended use. The study was carried out to establish the potential of rainwater harvesting in the University of Eldoret, motivated by the need for rationalization of water supply in the university due to population growth, increased expenditure on water and the need to complement total dependence on municipal water supply. The investigation examined what happens to rain falling in the campus and included measurement of the area of available rooftops, roof top catchment calculations, reviewing the amount and rainfall pattern for 10 consecutive years and estimating the storage that may be required for the rainwater harvested. The study established that there is a substantial potential for RWH through rooftop water harvesting in the University as the rainfall is adequate, the rainfall pattern reliable and enough rooftop surfaces already in place. The amount of rainfall received in the area per annum is substantial and can satisfy a significant portion of the University water supply while also saving the university a substantial amount of money.